PROFITABILITY ANALYSIS OF BAKED BUSINESS IN DEWANTARA DISTRICT, NORTH ACEH REGENCY (CASE STUDY: BUNDA LISA'S MILK SPONGE CAKE BUSINESS) - Frisko Mende Karina Padang; Muhammad Authar; Riani; Zuriani; Ade Firmansyah Tanjung (Jurnal Mahasiswa Agribisnis, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are an economic sector that plays a crucial role in supporting community economic growth, particularly in the food industry. One of the businesses operating in this sector is Bolu Susu Bunda Lisa in Dewantara District, North Aceh Regency, which produces various types of cakes such as milk sponge cake, banana cake, coconut cake, and bhoi, using wheat flour, eggs, sugar, and other supporting ingredients as the main raw materials. The decline in production since 2022, caused by rising raw material prices that were not followed by adjustments in selling prices, has led to a decrease in production volume and has affected both income and business efficiency. This study aims to analyze the profitability level of Bolu Susu Bunda Lisa using cost analysis, revenue, profit, Break Even Point (BEP), Margin of Safety (MOS), and Margin Income Ratio (MIR) approaches. The results show that the milk sponge cake product has a total production cost of Rp. 1,369,382.69 per production process, generating a profit of Rp. 340,617.31 with a profitability level of 20%. The coconut cake product has a total production cost of Rp. 424,438.56, with a profit of Rp. 85,561.44 and a profitability of 16.72%. The banana cake product has a total production cost of Rp. 428,570.73, generating a profit of Rp. 101,429.27 with a profitability level of 19.19%. Meanwhile, the bhoi product has a total production cost of Rp. 198,292.20, with a profit of Rp. 71,707.80 and the highest profitability level of 26.54%. Although all cake products contribute to the business revenue, there are differences in efficiency and profitability levels influenced by the production cost structure of each product. Products with lower production costs tend to have higher profitability levels compared to those with higher production costs, even if they generate greater revenue. This is due to differences in raw material usage, production processes, and cost efficiency for each type of product. Based on these findings, Bolu Susu Bunda Lisa business is still considered profitable and feasible for further development Keywords: BEP, Cake Business, MIR, MOS, MSMEs, Profitability.